Mitigating citrus fruit cracking: the efficacy of chelated calcium or silicon foliar fertilizers in ‘Okitsu no. 58’ citrus fruit - Wang, Tie; Tan, Liping; Chen, Zhaofang; Yang, Youting; Yuan, Ya; Zheng, Zhendong; Deng, Lijun; Zhang, Mingfei; Sun, Guochao; He, Siya; Wang, Jun; Xiong, Bo; et al. (Frontiers in Plant Science, 2024)
The ‘Okitsu No. 58’ citrus variety is highly prone to fruit cracking, which jeopardizes yield and results in economic losses. In this study, we investigated the impacts of spraying 5 distinct concentrations (0.1, 0.2, 0.3, 0.4, and 0.5 g/L) of chelated calcium (Ca) or silicon (Si) fertilizers at the young fruit stage (60-90 days after flowering, DAF) on fruit cracking and quality in the citrus variety ‘Okitsu No. 58’. The results showed either Ca or Si fertilizer treatments reduced fruit cracking. We found that all Ca and partial Si treatments (0.4 and 0.5 g/L) significantly promoted the accumulation of Ca content in the peel. Notably, Ca or Si treatments significantly reduced polygalacturonase (PG) activity and inhibited the production of water-soluble pectin (WSP) in the peel. Additionally, Ca or Si treatments elevated the superoxide dismutase (SOD) activity and decreased the malondialdehyde (MDA) content of the peels. Changes in these parameters likely contributed to strengthening the durability of peel cell wall constituents, thus enhancing the fruit’s resistance to fruit cracking. Overall, except for the C3 (0.3 g/L of Ca), Ca or Si fertilizers contributed to fruit conventional quality, mainly in terms of higher soluble sugars (SS) and SS/TA (titratable acid). Therefore, our findings will provide a reference for the prevention and control of citrus fruit cracking and the development of new fertilizers.